Random regression models in the evaluation of the growth curve of Simbrasil beef cattle - Mota, R.R.; Marques, L.F.A.; Lopes, P.S.; Silva, L.P. da; Hidalgo, A.M.; Leite, C.D.S.; Torres, R.A. (Genetics and Molecular Research, 2013)
Random regression models were used to estimate the types and orders of random effects of (co)variance functions in the description of the growth trajectory of the Simbrasil cattle breed. Records for 7049 animals totaling 18,677 individual weighings were submitted to 15 models from the third to the fifth order including as fixed effects sex, contemporary group, feeding regimen, and type of reproduction and as random effects additive direct genetic effect, animal permanent environment, maternal additive genetic effect, and maternal permanent environment. The best-fit model presented order five to additive direct genetic effect, animal permanent environment, and maternal additive effect, with 6 classes of residual variances, and the maternal permanent environment effect was not significant, likely owing to the low average number of calves per cow. However, the model chosen for the growth curve presents three classes of residual variances, because even not showing the best fit it is more parsimonious, in addition to promoting a more realistic estimate of heritability.
Keywords: (Co)variance functions; Residual variance; Heritability